Plasma Cystathionine and Risk of Incident Stroke in Patients With Suspected Stable Angina Pectoris. Issue 17 (4th September 2018) - Dhar, Indu; Svingen, Gard F.T.; Ueland, Per M.; Lysne, Vegard; Svenningsson, Mads M.; Tell, Grethe S.; Nygård, Ottar K.
Abstract : Background: Cystathionine is an intermediate product in the transsulfuration pathway and formed during the B6‐dependent conversion of methionine to cysteine. Elevated plasma cystathionine has been related to atherosclerosis, which is a major etiological factor for ischemic stroke. However, the role of cystathionine in stroke development is unknown. Therefore, we prospectively assessed the association of circulating levels of cystathionine with risk of total and ischemic stroke. Methods and Results: Two‐thousand thirty‐six patients (64% men; median age, 62 years) undergoing coronary angiography for suspected stable angina pectoris were included. Stroke cases were identified by linkage to the CVDNOR (Cardiovascular Disease in Norway) project. Hazard ratios with confidence intervals (95% confidence interval) were estimated by using Cox‐regression analyses. During 7.3 years of median follow‐up, 124 (6.1%) incident strokes were ascertained, which comprised 100 cases of ischemic stroke. There was a positive association of plasma cystathionine with risk of total stroke and ischemic stroke. Comparing the fourth versus the first cystathionine quartiles, age‐ and sex‐adjusted hazard ratios (95% confidence interval) were 2.11 (1.19–3.75) and 2.56 (1.31–4.99) for total and ischemic stroke, respectively. Additional adjustment for major stroke risk factors only slightly attenuated the associations, which tended to be stronger in patients without previous or existing atrial fibrillation at baseline (hazard ratio [95% confidence interval], 2.43 [1.27–4.65] and 2.88 [1.39–5.98] for total and ischemic stroke, respectively). Conclusions: In patients with suspected stable angina pectoris, plasma cystathionine was independently related to increased risk of total stroke and, in particular, ischemic stroke. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00354081.